Growth and topological branching of the soursop and manirote - Parés-Martínez, Jorge; Arizaleta, Miguel; Bautista, Damaso (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The objective of this work was to characterize growth and branching system of the soursop (Annona muricata) and manirote (Annona montana) rootstock plants, and grafted plants of Annona muricata on Annona montana. Length and number of branchs and node number produced by branches of first and second order, after each of two sequential pruning, were determined. A topologycal analysis of branching was performed after the first and second pruning, in which altitude, magnitude and total number of external branching were measured. Branches of the three evaluated materials presented similar tendency related to the length, node formation and lengthening. The formation of node increased gradually in time and the production of potentially productive branches of the A. muricata rootstock plants was greater than grafted ones. Plants showed a pattern of dichotomic and numerically scarce branching. The topologycal characteristics defined satisfactorily the type of branching that rootstock plants presented during the first and second pruning.